DOI: 10.14264/uql.2015.602
|View full text |Cite
|
Sign up to set email alerts
|

The living donor study: the concepts and frames of living kidney donors

Abstract: This thesis explores the concepts and frames of living kidney donors through the use of recorded and transcribed conversations between living kidney donor patients and their transplant team. It offers insight into the expectations of living kidney donors as they prepare themselves to gift a kidney to someone they know.Living kidney donor frames are represented as particularly resilient and well-defined, shielding them from messages delivered by their transplant team. Those frames incorporate their acceptance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 134 publications
1
2
0
Order By: Relevance
“…The need to protect their eligibility left some donors unwilling to disclose their concerns. Other studies have also found that directed and nondirected donors feel anxious about undergoing psychosocial assessment due to their determination to donate and attempt to manage how they are perceived, and some conceal experiences that might exclude them (16,22,25). We found that some donors who were men were overcome with anxiety before their operation, which supports findings from a study that used self-administered anxiety scales (26).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The need to protect their eligibility left some donors unwilling to disclose their concerns. Other studies have also found that directed and nondirected donors feel anxious about undergoing psychosocial assessment due to their determination to donate and attempt to manage how they are perceived, and some conceal experiences that might exclude them (16,22,25). We found that some donors who were men were overcome with anxiety before their operation, which supports findings from a study that used self-administered anxiety scales (26).…”
Section: Discussionsupporting
confidence: 85%
“…Some donors recalled ignoring information that contradicted their decision to donate. This reflects an analysis of the dialogue between potential donors and transplant professionals, which found that donors express disinterest in risk information, because their decision is "entrenched" (22). This accords with cognitive dissonance theory, the tendency to minimize inconsistency between our thoughts and actions (23).…”
Section: Discussionmentioning
confidence: 76%
“…1,9 Data provided by the First Central Hospital (December 2020) documented 1-and 3-y patient survival rates of 93.1% and 89.7 % after liver transplantation and 100% and 95.9% after kidney transplantation, respectively. 1,7 The Mongolian Pancreas Transplant Team completed their special training program at Asan Medical University in Korea in 2019. The team has thus far retrieved 3 deceased donor pancreata and plans for their first clinical pancreas transplant in 2021.…”
Section: Transplant Activitiesmentioning
confidence: 99%